An analysis of the contributions and premiums collection systems and financial performance of social security funds: a case study of NSSA Chinhoyi - Zindonda, Gelda (Midlands State University, 2018)
The research sought to analyze the contributions and premiums collection systems and their impact on financial performance in Social Security Funds being a case study of NSSA Chinhoyi. Some researchers were of the view that there is a relationship between collection systems and financial performance of Social Security Funds. However, other authors argued that there is no relationship, the causes of poor financial performance is influenced by other factors besides collection systems. In conducting the research, the researcher used descriptive research design which uses both qualitative and quantitative research instruments. Data was collected through the use of questionnaires and conducting interviews. The data collected was analyzed through the use of excel and the analysis indicated that there is need for effective collection system so as to improve financial performance. The researcher also concluded that there are other factors that influence financial performance besides collection systems such as corporate governance, internal controls and accounting practices that a firm adopts. The researcher recommends that there is need to have effective collection systems to ensure total compliance and remittance so as to improve financial performance of social security organizations.